Developing a Legal, Ethical, and Socially Responsible Mindset for Business Leadership - Mujtaba, Bahaudin G.; Cavico, Frank J.; Nonet, Guenola; Rimanoczy, Isabel; Samuel, Marissa (Advances in Social Sciences Research Journal, 2015)
One of the main responsibilities of educators is to prepare the future leaders for our communities and society so they can think of the legal, ethical, social, and environmental consequences of their decisions as managers and professionals. In other words, these future leaders must become great forecasters of the impact of their decisions, strategic choices and actions before they execute them. In order to instill ethical values in the minds of future business leaders, it is best to regularly and continuously socialize them with ethical and sustainability expectations from the outset. As such, this article proposes that educators should begin inculcating students through a mandatory “ethics” orientation at the beginning of their studies. Therefore, in this paper, the authors present an overview of an actual ethics orientation program for graduate students along with the overall benefits of it. Relevant recommendations and suggestions are provided for administrators, educators, and curriculum coordinators.